Supernatural monitoring and sanctioning in community-based resource management. Issue 2 (2nd April 2016) - Hartberg, Yasha; Cox, Michael; Villamayor-Tomas, Sergio
Abstract : Cooperation in human societies is difficult to sustain if mechanisms are not in place to monitor behavior and sanction transgressions. Unfortunately, these mechanisms constitute second-order public goods that are vulnerable to freeriding. Religion has been proposed to solve this problem by shifting these burdens to the realm of the supernatural. However, very little research has been done to examine the specific content of beliefs in supernatural monitoring and sanctions within real world cooperative contexts. To help fill this void and to better understand the role these institutions may have played in the development of prosociality, we performed a meta-analysis of case studies ( N = 48) in which religion played some role in community-based resource management (CBRM). Our findings suggest that beliefs in supernatural enforcement are common features of CBRM and that these duties are ascribed to entities ranging from ancestral spirits to gods. The specific sanctions believed to be imposed for violating rules are varied, but most often represent common occurrences that are readily open to interpretation as indications of supernatural efficacy. We propose that the provincial quality of the supernatural entities associated with CBRM may limit the scale at which they can promote prosociality and we discuss the implications this may have for the evolution of high gods.